IMPROVING TRANSITIONS IN CARE FOR CHILDREN WITH COMPLEX CARE NEEDS IN NOVA SCOTIA. (18th May 2018) - Curran, Janet; Vine, Jocelyn; Breneol, Sydney
Abstract: BACKGROUND: Children with complex care needs are a small yet resource intensive population in Canada. At present, there is wide variation in the way in which this population is characterized in the clinical and research literature. Transitions from hospital to home for these children can be complicated by variation in available services and resources in their home community; complex technological logistics; and a sharp disjuncture between discharge instructions provided to families and implementation in their home communities. OBJECTIVES: Develop policy recommendations for inclusion in a Nova Scotia strategy to support transitions in care for these children with medical complexity. DESIGN/METHODS: We used a mixed method design. During phase 1 we developed six cases representing children with different levels of complexity. Cases were informed by parent and provider interviews at 4 time points, chart audits and validated measures of caregiver distress. In phase 2, we conducted key stakeholder interviews across Nova Scotia to identify barriers and facilitators to successful transitions in care. A multi-sector consensus meeting was held during phase 3 to discuss study findings and refine key recommendations for inclusion in a Nova Scotia strategy. RESULTS: Six cases included children aged 15 days to 9 years old who were followed by as many as seven services and lived 50–300 km from IWK Health Centre. Key stakeholder interviews were conducted with 4 nurses, 4 physicians, and 1 administrator from 5 communities across Nova Scotia. A range of inter-institutional communication challenges and limited educational resources were identified as a key barrier. Participants identified the need for a nurse-coordinator role to act as a resource for both families and health providers in the community. A half-day consensus meeting 20 stakeholders from different health and government sectors was held. Proposed policy recommendations included: (1) consistent, timely, and discharge planning, (2) a comprehensive repository of resources for health care providers and families, (3) educational outreach strategy to build capacity for providers and families, (4) a nurse-coordinator role in each health zone to act a liaison and resource for health care providers and families, (5) work with existing provincial programs and services to develop policies and tools that are unique to a paediatric population, (6) adopt an established definitional framework for Children with Medical Complexity. CONCLUSION: Our collaborative patient-centred approach to understanding how children with complex care needs currently navigate transitions in care in Nova Scotia provided a foundation for developing recommendations for a provincial strategy.